Beyond the host: Unveiling the independent microbiome of equine gastrointestinal nematodes - Fabio Gentilini; Tolulope Grace Ogundipe; Maria Elena Turba; Noemi Romagnoli; Carlotta Lambertini; Claudia Pollera; Paola Cremonesi; Laura Stancampiano (PLoS ONE, 2026)
Gastrointestinal nematode infections significantly impact equine health and welfare, with rising anthelmintic resistance demanding alternative control strategies. Emerging evidence suggests that parasitic nematodes harbour distinct microbiomes, potentially influencing host-parasite dynamics and parasite survival. This study aimed to characterize and compare the microbiomes of equine gastrointestinal nematodes and their hosts, focusing on differences in composition, diversity, and core microbiota structure across different intestinal sites, nematode subfamilies, and sexes. Faecal and nematode samples were collected from equids ( Equus caballus and Equus asinus ) at slaughterhouses. DNA was extracted, and the V3-V4 regions of the 16S rRNA gene were amplified and sequenced using the Illumina iSeq 100 platform. Bioinformatic analyses were performed with QIIME2 and MicrobiomeAnalyst, and statistical comparisons employed PERMANOVA, LEfSe, and alpha and beta diversity metrics. Nematodes exhibited a distinct microbiome dominated by Firmicutes, Proteobacteria, Bacteroidota, Verrucomicrobiota, and Actinobacteriota, differing significantly from the faecal microbiota. Alpha diversity analyses revealed lower richness in nematodes, while beta diversity indicated distinct community structures (p = 0.007). Microbial composition varied by gastrointestinal site, nematode subfamily, and sex. Proteobacteria were consistently enriched in nematodes, particularly in the caecum. Core microbiome analysis identified exclusive nematode-associated taxa such as Fusobacterium , Mesorhizobium , and Mycoplasma . Equine gastrointestinal nematodes harbour independent and structured microbiomes, distinct from those of their hosts. These findings underscore the ecological specialization of nematodes and highlight the potential of targeting parasite-associated microbiota for novel control strategies.